Selected Properties of Araucaria angustifolia and Araucaria araucana Seed Protein - Conforti, Paula Andrea (2011)
Araucaria angustifolia and Araucaria araucana are coniferous trees with large and nutritious seeds. The structure and nutritional properties of the proteins of these seeds were studied. About 70% of the proteins of the gametophyte were soluble in distilled water, although their solubility decreased drastically in raw seed flour. The protein components of both araucaria seeds were very similar; the main protein species have molecular weights of 14, 24, and 30 kDa. These proteins have a high nutritional quality, being triptophan the first limiting amino acid.